The Effect of Teaching Ability, Technology use and Social Support on the Performance of Teachers at MTSN 2 Kerinci with Work Motivation as an Intervening Variable - Ahmad Sunafis Al Haziz; Yulasmi, Yulasmi; Lusiana, Lusiana (Jurnal Multidisiplin Sahombu, 2025)
This study aims to examine the influence of teaching ability, technology use, and social support on teacher performance at MTSN 2 Kerinci, with work motivation as an intervening variable. Data collection methods included a survey and questionnaire distribution, with a sample of 61 respondents. The analysis method used was structural equation modeling using SmartPLS. The results showed a significant effect of teaching ability on work motivation at MTSN 2 Kerinci. There was an insignificant effect of technology use on work motivation at MTSN 2 Kerinci. There was an insignificant effect of social support on work motivation at MTSN 2 Kerinci. There was a significant effect of teaching ability on teacher performance at MTSN 2 Kerinci. There was a significant effect of technology use on teacher performance at MTSN 2 Kerinci. There was a significant effect of social support on teacher performance at MTSN 2 Kerinci. There was a significant effect of work motivation on teacher performance at MTSN 2 Kerinci. Work motivation mediated the effect of teaching ability on teacher performance at MTSN 2 Kerinci. Work motivation did not mediate the effect of technology use on teacher performance at MTSN 2 Kerinci. Work motivation does not mediate the effect of social support on teacher performance at MTSN 2 Kerinci.